2020
DOI: 10.1088/1742-6596/1422/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Individual Learning Plans Program Evaluation of Planning Education in Junior High School: Discrepancy Model

Abstract: Learning Plans (ILP) is a guidance and counseling program that can be used to help learners educational planning and decision making further studies SMA / MA / SMK. In order to implement professional programs, the program organized by following the rules of implementation of ILP existing program. However, the implementation of the ILP program on educational planning of students in the school are not just using established standards. Describe research purposes disparities in aspects of the preparation, organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Eğitimin planlamasına yönelik çalışmalar yönetimden bağımsız olarak görülmemiş ve eğitim kurumlarının kalitelerinin artırılmasına (Ghatole ve Dahikar, 2020), akademik takvim ve eğitim programlarının planlanmasına (Sugianto, 2020), eğitim sisteminde yer alacak çalışanların eğitiminin planlanmasına (Yulianti ve Munir, 2020) yönelik çalışmalar yapılmıştır.…”
Section: Eğitim Yönetimi Denetimi Planlaması Ve Ekonomisi Alanlarınınunclassified
“…Eğitimin planlamasına yönelik çalışmalar yönetimden bağımsız olarak görülmemiş ve eğitim kurumlarının kalitelerinin artırılmasına (Ghatole ve Dahikar, 2020), akademik takvim ve eğitim programlarının planlanmasına (Sugianto, 2020), eğitim sisteminde yer alacak çalışanların eğitiminin planlanmasına (Yulianti ve Munir, 2020) yönelik çalışmalar yapılmıştır.…”
Section: Eğitim Yönetimi Denetimi Planlaması Ve Ekonomisi Alanlarınınunclassified
“…The limitation of Ngala et al's research was not yet showing the evaluation standards in detail and had not been able to show the dominant indicators that trigger the successful implementation of distance education; (5) research conducted in 2019 by Siswadi et al [9] showed the limitations of the CIPP model, especially on aspects in the context component and the input component used in evaluating national standards of nursing education. Besides, in research of Siswadi et al also has not shown any aspects or indicators that trigger the effectiveness of learning in nursing education; (6) research conducted in 2020 by Sugianto [10] showed the utilization of the discrepancy model used to evaluate individual learning programs at junior high school level. The findings obtained in Sugianto's research were two aspects of individual learning programs that were unsuitable to program standards.…”
Section: Introductionmentioning
confidence: 99%
“…The intended evaluation model is the Discrepancy-Tat Twam Asi model, which is integrated with the TOPSIS method calculations to obtain the dominant indicator determining blended learning effectiveness. The Discrepancy-Tat Twam Asi model is a combination of the educational evaluation model (Discrepancy) with one of the Balinese local wisdom concepts (Tat Twam Asi).The Discrepancy model is one of the evaluation models that provide recommendations based on gaps found from the evaluation results that are compared to established evaluation standards [8,9,10,11]. Tat Twam Asi is a concept of the Balinese people's local wisdom that shows the existence of tolerance, equal rights, or the same authority among human beings to create harmony [12,13,14].…”
Section: Introductionmentioning
confidence: 99%